Financial Ratios, Economic Value Added and Market Reaction: A Quantitative Study on Indonesia Stock Exchange - Azis, Indrawan; Nianty, Dara Ayu; Marlinah, Andi (Pusat Penerbitan dan Publikasi Ilmiah Fakultas Ekonomi, Universitas Muslim Indonesia, 2020)
Reflecting on the phenomenon of stock market movements on the Indonesia Stock Exchange, this study was appointed to examine the effect of the effect of liquidity, solvency, and Economic Value Added (EVA) on market reactions in manufacturing companies listed on the IDX. The research method uses a quantitative approach, and types are categorized in explanatory research. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange in the period 2017-2019. Determination of the sample to be tested in this study using a purposive sampling method and obtained 36 companies. Secondary data were obtained from the Capital Market Information Center (PIPM) the Indonesia Stock Exchange (IDX). The analytical method is Partial Least Square (PLS) with the assistant of SmartPLS 3.0 software. The results of the study showed that all exogenous variables positively and significantly influenced endogenous variable (EVA and Market Reaction). Research findings enrich previous studies on understanding market reactions and their impact on the development of corporate financial strategies in Indonesia.